Philosophical Foundations of Project Based Learning: Perspectives on Constructivism and Contextualism Theory - Siska, Felia; Asnimawati , Asnimawati; Sulkaisi, Neffi; Novidyayulanda; Morales, Janice Zamora (SOSEARCH : Social Science Educational Research, 2024)
The purpose of this study is to analyze the role of constructivism and contextualism theory as a philosophical foundation in the application of Project Based Learning and to identify challenges and opportunities in its implementation in the current education system. The method used in this study is a literature review that examines various current literature related to PBL, constructivism theory, and contextualism, as well as its application in 21st century education. The results show that Project Based Learning based on both theories can increase student engagement, deepen their understanding through hands-on experience, and connect learning with real-life contexts. However, challenges such as limited resources, time, and resistance to change are still obstacles to its implementation. However, the opportunity to optimize PBL, especially by utilizing technology, is huge in creating learning that is more flexible and relevant to the times. Conclusion: Project Based Learning based on constructivism and contextualism is effective in increasing student engagement and understanding, even though it is constrained by resources and resistance, but technology opens up optimization opportunities.